O Jornalismo nas Rádios Comunitárias - Rosembach, Cilto José (2006)
The present study analyzes journalism in community radios from the paradigm of alternative, grassroots communication. The analysis is done from the historical context of community radios in Brazil. This work uses the case study as the methodological basis and examines the programming of community journalism in two community radios in the state of São Paulo from a theoretical reference that clarifies grassroots communication and emphasizes the concepts of community journalism. Two community stations, Radio Cantareira FM 107.5 Vila Isabel, District of Brasilândia, São Paulo, capital, on the air since 1995 and Radio Nova Esperança FM 87.9, Vila Esperança, Cubatão, São Paulo, on the air since 2003, are analyzed. In the final considerations, based on the studies done, we present the possibilities of the contribution of community journalism to the democratization of communication, and to the construction of citizenship. It also shows the limits and challenges of this paradigm of communication